Steel Building Friction Connection Seismic Performance – Corrosion Effects. (June 2019) - Chanchi Golondrino, Jose Christian; MacRae, Gregory Anthony; Chase, James Geoffrey; Rodgers, Geoffrey William; Scott, Allan Charles Nye; Clifton, George Charles
Abstract: Asymmetric Friction Connections (AFCs) dissipate energy in structural systems. Surface treatments and severe corrosion effects on AFC strength, and the corrosion mechanism of AFCs have not been explained yet. A total of 12 AFCs were surface treated, exposed to a severe corrosive regime, and cyclically loaded. Surface treatments, such as cleaned, sweep blasted, alkyd coated, and zinc coated surfaces were considered. AFC strength and the stability of the hysteresis loop of the connection were sensitive to both surface treatment and corrosion. AFCs developed general, crevice, and filiform corrosion not only at the external surfaces, but also at the internal clamped surfaces for some surface treatments. As a result of corrosion, connection strength increased at the initial sliding cycles up to 100%, 120%, 130%, and 50% for cleaned, sweep blasted, alkyd coated, and zinc coated surfaces, respectively. After the corrosive product is removed by the sliding of the slotted plate, the connection strength returned to approximately the strength of the non-corroded connections. These results were used to propose a model to predict the maximum and minimum likely AFC strengths when plate surfaces of the plates are treated, and when these four surface treatments are severely corroded. The experimental results, and resulting model, provide significant insight and design tools for the practical use of AFCs in design. Highlights: Asymmetrical Friction Connections were surface treated, corroded, and cyclically tested. Corrosive mechanisms of Asymmetrical Friction Connections are described. Asymmetrical Friction Connections developed general, crevice, and filiform corrosion. Asymmetrical Friction Connection strength depends on surface treatment and corrosion. Asymmetrical Friction Connection strength model considering surface treatment and corrosion is proposed.